Sikkim State Annual Plan 1991-92 Statistical Supplement for 8th Five Year Plan 1990-95 and Annual Plan 1991-92 - Planning Commission (Planning Commission, 1990)
The State’s Draft Eighth Five Year Plan had been formulated in keeping with the thrust and direction adopted in the approach paper which has been approved by the National Development Council. The document being consistent with the emphasis and thrust as underlined in the Approach Paper to the Eighth Five Year Plan may be considered as the basis for discussion on the proposals for the Five-Year Plan pertaining to the State.
Planning and Development Department, Government of Sikkim